A critical analysis and evaluation of the O.P. Sienna Archives practices - Bumangabang, Wilma T. (2003)
A well-documented and unprejudiced study of its own past makes the Church more "expert in humanity" because it reveals the historical richness that lies behind her and allows her to identify herself with her essential, continuing and varied mission of inculturation and acculturation. A study conducted such as this, which proceeds from a careful collection of all that can be documented, helps out in planning a future founded on the contribution whereby memory is also prophecy. Thus, the documents preserved in the archives represent, and becomes an immense and precious heritage.